The relationship between job satisfaction, work-life balance and organizational commitment on employee performance / Hussein Isse Hassan Abdirahman …[et al.] - Hassan Abdirahman, Hussein Isse; Najeemdeen, Iliyasu Shiyanbade; Abidemi, Bello Taofik; Ahmad, Roshidah (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2018)
The study examines the influence of work-life balance, job satisfaction and organizational commitment on employee performance among administrative staff in Northern region universities in Malaysia. The study adopted quantitative research method, collecting the data from two hundred and seventy-one administrative staff respondents by using probability sampling technique. Data collected were analysed using Statistical Package for Social Science (SPSS). The data were analysed using different statistical techniques such as reliability analysis, descriptive analysis, correlation analysis (Pearson Correlation Analysis) and regression analysis (Multiple Regression Analysis). The regression results indicate that all independent variables which are work-life balance, job satisfaction and organizational commitment are positively correlated with the dependent variable which is employee performance. However, the study concludes that for effective employee performance to be enhanced, the level of motivation needs to be improved. This would determine the sustainability of organizational goals either in private or public sector.